The effect of venue and wind on the distance of a hammer throw - Hunter, I. (Research Quarterly for Exercise and Sport, 2005)
Es wird dargelegt, welche Auswirkungen Wurfanlage und Wind auf die Wurfweite im Hammerwerfen haben.